The Harms of State, Free-Market Common Sense and COVID-19. (1st April 2021) - Coleman, Roy; Mullin-McCandlish, Beka
Abstract : The markedly high levels of preventable death and injury from COVID-19 in the UK have been refracted by government appeals to "British common-sense" in response to the crisis. We critically explore this appeal as a generator of harm continuous with free-market common-sense (FMCS) that stretches back to the start of the 1980s and the Thatcherite assault on state protections, "enemies within" and expertise in the public realm, driving and legitimating a broad landscape of harm under neoliberal restructuring. This is the context for understanding government responses to COVID-19 and the Grenfell fire, both of which have resulted in avoidable death and injury and both of which illustrate the role of "common-sense" in the demonisation and blaming of the victims of state violence along with a deligitimation of expertise in public health. Following Gramsci's conceptualisation of common-sense and its role in cultivating a never-guaranteed consensus for the continuance of capitalist state power, we explore the emergence of Gramsci's "good sense" in the current juncture and its challenge to the harms of state that FMCS has generated.